Chemical profiling of volatile compounds of the essential oil of grey-leaved rockrose (Cistus albidus L.) and its antioxidant, anti-inflammatory, antibacterial, antifungal, and anticancer activity in vitro and in silico - Elbouzidi, Amine; Taibi, Mohamed; Laaraj, Salah; Loukili, El Hassania; Haddou, Mounir; El Hachlafi, Naoufal; Naceiri Mrabti, Hanae; Baraich, Abdellah; Bellaouchi, Reda; Asehraou, Abdeslam; Bourhia, Mohammed; Nafidi, Hiba-Allah; et al. (Frontiers in Chemistry, 2024)
Cistus albidus L., also known as Grey-leaved rockrose and locally addressed as šṭab or tûzzâla lbîḍa, is a plant species with a well-established reputation for its health-promoting properties and traditional use for the treatment of various diseases.This research delves into exploring the essential oil extracted from the aerial components of C. albidus (referred to as CAEO), aiming to comprehend its properties concerning antioxidation, anti-inflammation, antimicrobial efficacy, and cytotoxicity. Firstly, a comprehensive analysis of CAEO's chemical composition was performed through Gas Chromatography-Mass Spectrometry (GC-MS). Subsequently, four complementary assays were conducted to assess its antioxidant potential, including DPPH scavenging, β-carotene bleaching, ABTS scavenging, and total antioxidant capacity assays. The investigation delved into the anti-inflammatory properties via the 5-lipoxygenase assay and the antimicrobial effects of CAEO against various bacterial and fungal strains. Additionally, the research investigated the cytotoxic effects of CAEO on two human breast cancer subtypes, namely MCF-7 and MDA-MB-231. . Chemical analysis revealed camphene as the major compound, comprising 39.21% of the composition, followed by α-pinene (19.01%), bornyl acetate (18.32%), tricyclene (6.86%), and melonal (5.44%). Notably, CAEO exhibited robust antioxidant activity, as demonstrated by the low IC50 values in DPPH (153.92 ± 4.30 µg/mL) and β-carotene (95.25 ± 3.75 µg/mL) assays, indicating its ability to counteract oxidative damage. The ABTS assay and the total antioxidant capacity assay also confirmed the potent antioxidant potential with IC50 values of 120.51 ± 3.33 TE µmol/mL and 458.25 ± 3.67 µg AAE/mg, respectively. In terms of anti-inflammatory activity, CAEO displayed a substantial lipoxygenase inhibition at 0.5 mg/mL. Its antimicrobial properties were broad-spectrum, although some resistance was observed in the case of Escherichia coli and Staphylococcus aureus. CAEO exhibited significant dose-dependent inhibitory effects on tumor cell lines in vitro. Additionally, computational analyses were carried out to appraise the physicochemical characteristics, drug-likeness, and pharmacokinetic properties of CAEO's constituent molecules, while the toxicity was assessed using the Protox II web server.